Transient Thermal Analysis of a Solar-Assisted AHU by Focusing on Heat Recovery and Nanoparticles: Jeddah Climate Zone - Khetib, Yacine (Frontiers in Energy Research, 2021)
In Jeddah climate region, a lot of energy is assigned to the air handling unit (AHU) sector, which should be reduced by using energy-efficient solutions. As the air passes through the cooling coil, a lot of energy is consumed to reduce the temperature along with humidity so that if the air is pre-cooled in the previous stages, energy consumption in this energy-intensive section will be diminished. Using the coldness of the return air in the heat recovery unit (HRU), the incoming air is pre-cooled. Based on the thermodynamic calculations, in June, July and August, the cooling coil power demand reduces by 11.6, 13.3 and 12%. In summer, owing to using HRU, an energy-saving by 76.08-MWh is achieved (12.34% reduction in energy demand). By incorporation of the solar collectors in AHU, heating coil demand diminishes by 1206, 1399 and 1367 kWh in June, July and August respectively. To improve the solar-assisted AHU effectiveness, MWCNT nanoparticles are injected into the collectors and it is found that the saving-energy capability improves by 17.7% using MWCNT-water at 0.1 vol.%.